A multifunctional coating material for concrete structure surfaces affected by backwater pressure
By using multifunctional coating materials, the existing waterproof coatings have been solved for the short service life and prone to mildew on the surface of concrete structures affected by backwater pressure, and the comprehensive effects of high bond strength, waterproof, mildewproof and air purification are achieved.
Patent Information
- Application Number
- CN202411924266.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
AI Technical Summary
The existing waterproof coatings used for concrete structure surfaces affected by backwater pressure have short service life, are prone to mildew and have a relatively single function, and cannot effectively prevent mold growth and air pollution.
A multifunctional coating material is used, and its composition includes phosphomatate cement, fly ash, limestone machine sand, acid-etched modified nanotitanium dioxide or its composite, cyanite powder, fluorocarbon resin, ultra-high molecular weight polyethylene fiber and ternary high-efficiency retarder. After mixing through a vibration mixer, ash shovel is used to apply on the surface of the concrete structure.
The coating formed by this coating material has high bond strength and toughness, which can effectively prevent moisture penetration and mold growth, and also has air purification function, which can catalyze the decomposition of harmful gases under daily light conditions and extend service life.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of architectural coatings, and in particular to a multifunctional coating material used for the surface of a concrete structure affected by back water pressure. Background Art
[0002] Concrete structures affected by back water pressure include military underground bunkers, basements, underground parking garages, hydraulic underground plant buildings and other concrete structures. Due to long-term groundwater pressure, rainfall and poor air circulation in the space, the interior is damp, harmful substances in the air accumulate for a long time, and mold microorganisms grow. In the long run, it is easy to cause harm to the health of internal workers and precision instruments and equipment.
[0003] At present, the surface of concrete structures affected by backwater pressure is only treated with waterproof mortar or waterproof coatings, such as acrylic coatings, polyurea coatings and other common waterproof materials. Such waterproof measures have solved the water seepage problem of backwater structures to a certain extent, but there are still problems such as short life, easy to fall off and crack, and easy to mold on the surface. In addition, the function of the material is relatively single and cannot purify the air environment inside the concrete structure. There is a lack of a multifunctional coating material with a long service life that can simultaneously play a role in waterproofing, moisture-proofing, and mildew-proofing, and purifying the indoor air of the concrete structure. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a multifunctional coating material for the surface of concrete structures affected by back water pressure, which solves the technical problems that the waterproof coatings currently used on the surface of concrete structures affected by back water pressure have short service life, are prone to mildew, and have relatively single functions.
[0006] (II) Technical solution
[0007] In the first aspect, the present invention provides a multifunctional coating material for the surface of a concrete structure affected by back water pressure, which comprises, by mass percentage, 30-40% phosphate magnesium cement, 10-15% fly ash, 30-40% limestone machine-made sand, 5-10% acid-etched modified nano titanium dioxide or its composite, 5-10% kyanite powder, 3-5% fluorocarbon resin, 0.5-1% ultra-high molecular weight polyethylene fiber and 0.5-1% ternary high-efficiency retarder; the multifunctional coating material is a powder material. Before use, pure water is added according to a water-cement ratio of 0.38-0.42, and a vibrating mixer is used to mix and stir for 2-3 minutes, and a ash shovel is used to apply and scrape the surface of the concrete structure affected by back water pressure, and the coating thickness should not be greater than 5mm.
[0008] According to a preferred embodiment of the present invention, the fineness of the magnesium phosphate cement is below 80 μm, that is, the percentage passing through the 80 μm sieve should be greater than 90%, and the specific surface area is 300-400 m 2 / kg. As a binder, magnesium phosphate cement provides higher bonding force and strength, while helping to improve the waterproof performance of the coating and increase the early strength development speed of the coating; its preferred content in the coating is 32-36%.
[0009] According to a preferred embodiment of the present invention, the average particle size of fly ash is less than 10 μm, 70% of the particles should be able to pass through a 45 μm sieve, and the specific surface area is 300-600 m 2 / kg. Fly ash is used to improve the fluidity of the coating, reduce crack formation, increase durability and impermeability, and work synergistically with a higher proportion of magnesium phosphate cement to optimize the reaction product, repairing, water blocking and bonding the surface of the concrete structure; its preferred content in the coating is 12-15%.
[0010] According to a preferred embodiment of the present invention, the maximum particle size of the limestone machine-made sand is 0.3 mm, which plays a filling and aggregate role for the coating material, enhances the mechanical strength and wear resistance of the coating, and is combined with a high proportion of magnesium phosphate cement to maintain the structural stability of the coating material layer. At the same time, it can fill the small cracks on the surface of the concrete structure affected by the back water pressure. The preferred content of limestone machine-made sand in the coating material is 32-36%. Preferably, the limestone machine-made sand contains 1-5% (total amount of coating material) of magnesium carbonate. Compared with machine-made sands such as silicon dioxide, limestone machine-made sand has porosity and a certain alkalinity. Limestone machine-made sand has adsorption properties and can adsorb organic molecules and some acidic gas molecules in the air.
[0011] According to a preferred embodiment of the present invention, the particle size of the acid-etched modified nano titanium dioxide does not exceed 100nm, and the specific surface area is extremely large, reaching 50-250m 2 / g(50000-250000m 2 / Kg). Acid-etched modified nano titanium dioxide gives the coating self-cleaning and air purification functions, and can catalytically decompose organic pollutants in the air under extremely weak light, improving the antibacterial and anti-mildew properties of the coating material layer. The preferred content of nano titanium dioxide in the coating material is 7-9%. After acid-etched modification, nano titanium dioxide can catalytically decompose bacteria, nitrogen oxides, formaldehyde and organic matter in the air under light irradiation even in basements, underground parking garages, and underground water conservancy workshops where sunlight cannot reach.
[0012] When the acid-etched modified nano-titanium dioxide is exposed to ultraviolet light or certain types of visible light, it can generate electron-hole pairs (i.e., carriers). These carriers can trigger a series of redox reactions to generate reactive oxygen species (ROS), such as superoxide anions, hydroxyl radicals, etc. These reactive oxygen species have extremely strong oxidizing ability and can destroy the cell membrane or cell wall of microorganisms, causing the leakage of cell contents, thereby killing bacteria, fungi and other microorganisms. In addition to the antibacterial and anti-mildew effects, the reactive oxygen species generated by photocatalysis can also decompose organic pollutants and give the coating material layer the ability to self-clean.
[0013] Acid-etched modified nano-titanium dioxide can be purchased from commercial sources or prepared as follows:
[0014] Take rutile nano-TiO2 as raw material, use at least one of inorganic acids (nitric acid, sulfuric acid, hydrochloric acid) as an acid etchant, and the concentration is 0.1M-6M. Disperse nano-TiO2 in an appropriate amount of deionized water to form a suspension, slowly add acid solution to the suspension, and continue stirring to ensure uniform mixing, control the temperature at 35-85℃ for 0.5-3h to carry out sufficient acid etching. During this period, the acid reacts with the surface of nano-TiO2, removes surface impurities and introduces new functional groups, thereby changing its surface properties. After the acid etching treatment is completed, wash the sample with deionized water until the pH value of the washing water is close to neutral to remove residual acid and other soluble substances, centrifuge or filter and collect, dry, and calcine in air at 400-600℃ for 1-3h to further stabilize the structure or enhance performance.
[0015] According to a preferred embodiment of the present invention, the acid-etched modified nano-titanium dioxide composite is an acid-etched modified nano-titanium dioxide-cerium oxide composite fiber, and its preparation method is:
[0016] Acid-modified nano titanium dioxide and cerium oxide powder are mixed in a mass ratio of 3:1-2, dispersed in water, and 10-20wt% of PVP by water mass is added to obtain a spinning solution, and electrostatic spinning is performed; the electrostatic spinning monomer conditions are: a spinning voltage of 10-20KV, a spinning distance of 13-16cm, and titanium dioxide-cerium oxide / PVP fibers are obtained; then, the titanium dioxide-cerium oxide / PVP fibers are heated to 750-850°C at 3-5°C / min for aerobic calcination to obtain acid-modified nano titanium dioxide-cerium oxide composite fibers.
[0017] According to a preferred embodiment of the present invention, the particle size of kyanite powder is 1-10 μm, which mainly provides the coating material layer with additional hardness, strength and thermal stability, and contributes to the long-term stability and crack resistance of the coating material layer. The preferred content of kyanite powder in the coating material is 6-8%.
[0018] Kyanite is an aluminum silicate mineral with the chemical formula Al2SiO5. Kyanite powder is a fine powder obtained by grinding Kyanite. Kyanite powder is a high-aluminum mineral. When Kyanite powder is used together with phosphate-magnesium cement, the phosphate-magnesium cement can act as an activator to promote the reactivity of Kyanite powder and enhance the overall performance of the material, especially the later strength of the coating.
[0019] Furthermore, 3-5% of the mass of the coating material is added to the coating material with a fluorocarbon resin to improve the hydrophobic effect of the coating material, reduce the surface humidity of the coating material layer and the air humidity of the basement, and achieve the effect of preventing algae, bacteria and mildew. The fluorocarbon resin is polyvinylidene fluoride PVDF, fluorinated ethylene propylene copolymer FEVE or hexafluoropropylene-vinyl ether copolymer, and preferably FEVE and hexafluoropropylene-vinyl ether copolymer are applied in combination according to 3-5:1-2. FEVE has excellent weather resistance, is easy to apply and has high coating hardness, and hexafluoropropylene-vinyl ether copolymer has good corrosion resistance and is suitable for use in extreme environments.
[0020] Kyanite powder can be used as a filler to fill the gaps in the coating, making the coating denser and smoother. A denser coating can reduce the chance of water penetration, thereby helping to improve the overall waterproof performance. Kyanite powder works synergistically in combination with fluorocarbon resin to further enhance the hydrophobic properties of the coating material. According to a preferred embodiment of the present invention, the length of the ultra-high molecular weight polyethylene fiber is 3-19 mm; the diameter is about 10-40 μm. The molecular weight of the ultra-high molecular weight polyethylene fiber is 3 million to 6 million Daltons, which is used to increase the toughness and mechanical strength of the coating material layer and improve the impact resistance. On the one hand, it is beneficial to repair cracks on the surface of the concrete structure affected by back water pressure, and on the other hand, it can also reduce shrinkage cracks in the coating material layer itself caused by sudden changes in humidity. Its preferred content in the coating material is 0.7-0.9%.
[0021] According to a preferred embodiment of the present invention, the ternary high-efficiency retarder is a combination of borax, calcium chloride and sodium phosphate in a mass ratio of 3-4:4-5:3-4, preferably 3:4:3. The ternary high-efficiency retarder is a micron-level fine powder. In the coating material, it is mainly used to delay the speed of cement hydration reaction and adjust the setting time, so that the prepared coating slurry has a longer construction time, and helps to avoid stress concentration caused by rapid solidification and improve the mechanical strength of the coating material layer. The preferred content of the ternary high-efficiency retarder in the coating material is 0.6-0.8%.
[0022] (III) Beneficial effects
[0023] The coating material of the present invention adopts phosphate magnesium cement as the main material, and is added with fly ash, limestone machine-made sand, acid-etched modified nano titanium dioxide or its composite, kyanite powder, ultra-high molecular weight polyethylene fiber and ternary high-efficiency retarder, etc. The coating formed by the coating material has high bonding strength and toughness. The synergistic effect of the kyanite powder and the fluorocarbon resin can ensure that even if there are fine cracks inside the coating, it is not easy for water to seep in, and condensation dew is prevented from appearing on the surface of the coating. It can effectively reduce the humidity of basements, hydraulic underground workshops and other spaces affected by back water pressure. The acid-etched modified nano titanium dioxide or its composite is treated with a special process so that it has strong oxidizing properties under the lighting conditions of daily lighting lamps, which is beneficial to purifying harmful gases in underground spaces and preventing mold from growing on the surface of concrete structures. It is effective for a long time and its catalytic degradation ability is not easy to decay. DETAILED DESCRIPTION
[0024] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with specific implementation methods.
[0025] Example 1
[0026] This embodiment provides a multifunctional coating material for the surface of a concrete structure affected by back water pressure, which is composed of 35% phosphate magnesium cement, 10% fly ash, 32% limestone machine-made sand, 9% acid-etched modified nano titanium dioxide, 10% kyanite powder, 3% FEVE (fluorocarbon resin), 0.5% ultra-high molecular weight polyethylene fiber and 0.5% ternary high-efficiency retarder, which is a micron-sized fine powder obtained by combining borax, calcium chloride and sodium phosphate in a mass ratio of 3:4:3.
[0027] The above-mentioned magnesium phosphate cement, limestone machine-made sand, fly ash, kyanite powder, and ultra-high molecular weight polyethylene fiber are all commercially available products. The fineness of magnesium phosphate cement is: the percentage passing through an 80 μm sieve should be greater than 90%, and the specific surface area is 300-400 m 2 / kg. The average particle size of fly ash is less than 10μm, 70% of the particles should be able to pass through a 45μm sieve, and the specific surface area is 300-600m 2 / kg. The maximum particle size of limestone machine-made sand (containing 1-5% of magnesium carbonate by weight of the coating material) is 0.3mm. The particle size of kyanite powder is 1-5μm. The length of ultra-high molecular weight polyethylene fiber is 3-19mm; the diameter is about 10-40μm. The molecular weight of ultra-high molecular weight polyethylene fiber is 3 million-6 million Daltons.
[0028] The particle size of the acid-etched modified nano-titanium dioxide does not exceed 100nm, and the specific surface area reaches 150m 2 / g, the preparation method is: using rutile nano-TiO2 as raw material, dispersing nano-TiO2 in an appropriate amount of deionized water to form a suspension, slowly adding 5M sulfuric acid solution to the suspension, and continuously stirring to ensure uniform mixing, controlling the temperature to 60℃ for 2h, washing the sample with deionized water until the pH value of the washing water is close to neutral, filtering and collecting, drying, and calcining in air at 550℃ for 2h.
[0029] Example 2
[0030] This embodiment provides a multifunctional coating material for the surface of a concrete structure affected by back water pressure, which is composed of 32% phosphate magnesium cement, 10% fly ash, 36% limestone machine-made sand, 8% acid-etched modified nano titanium dioxide, 10% kyanite powder, 3% hexafluoropropylene-vinyl ether copolymer (fluorocarbon resin), 0.5% ultra-high molecular weight polyethylene fiber and 0.5% ternary high-efficiency retarder. The ternary high-efficiency retarder is a micron-sized fine powder obtained by combining borax, calcium chloride and sodium phosphate in a mass ratio of 3:4:3. Among them, the specifications of each component and the preparation method of acid-etched modified nano titanium dioxide are the same as those in Example 1.
[0031] Example 3
[0032] This embodiment provides a multifunctional coating material for the surface of a concrete structure affected by back water pressure, which is composed of 40% phosphate magnesium cement, 10% fly ash, 30% limestone machine-made sand, 10% acid-etched modified nano titanium dioxide, 5% kyanite powder, 3.5% hexafluoropropylene-vinyl ether copolymer (fluorocarbon resin), 1% ultra-high molecular weight polyethylene fiber and 0.5% ternary high-efficiency retarder. The ternary high-efficiency retarder is a micron-sized fine powder obtained by combining borax, calcium chloride and sodium phosphate in a mass ratio of 3:4:3. Among them, the specifications of each component and the preparation method of acid-etched modified nano titanium dioxide are the same as those in Example 1.
[0033] Example 4
[0034] This embodiment provides a multifunctional coating material for the surface of a concrete structure affected by back water pressure, which is composed of 30% phosphate magnesium cement, 10% fly ash, 40% limestone machine-made sand, 8% acid-etched modified nano titanium dioxide, 7% kyanite powder, 3% FEVE (fluorocarbon resin), 1% ultra-high molecular weight polyethylene fiber and 1% ternary high-efficiency retarder by mass percentage. The ternary high-efficiency retarder is a micron-sized fine powder obtained by combining borax, calcium chloride and sodium phosphate in a mass ratio of 3:4:3. Among them, the specifications of each component and the preparation method of acid-etched modified nano titanium dioxide are the same as those in Example 1.
[0035] Example 5
[0036] This embodiment provides a multifunctional coating material for the surface of a concrete structure affected by back water pressure, which is composed of 36% phosphate magnesium cement, 10% fly ash, 32% limestone machine-made sand, 9% acid-etched modified nano titanium dioxide, 7% kyanite powder, 5% FEVE (fluorocarbon resin), 0.5% ultra-high molecular weight polyethylene fiber and 0.5% ternary high-efficiency retarder by mass percentage. The ternary high-efficiency retarder is a micron-sized fine powder obtained by combining borax, calcium chloride and sodium phosphate in a mass ratio of 3:4:3. Among them, the specifications of each component and the preparation method of acid-etched modified nano titanium dioxide are the same as those in Example 1.
[0037] Example 6
[0038] This embodiment provides a multifunctional coating material for the surface of a concrete structure affected by back water pressure, which is composed of 32% phosphate magnesium cement, 15% fly ash, 32% limestone machine-made sand, 8% acid-etched modified nano titanium dioxide, 8% kyanite powder, 4% FEVE (fluorocarbon resin), 0.5% ultra-high molecular weight polyethylene fiber and 0.5% ternary high-efficiency retarder by mass percentage. The ternary high-efficiency retarder is a micron-sized fine powder obtained by combining borax, calcium chloride and sodium phosphate in a mass ratio of 3:4:3. Among them, the specifications of each component and the preparation method of acid-etched modified nano titanium dioxide are the same as those in Example 1.
[0039] Example 7
[0040] In this embodiment, the acid-etched modified nano-titanium dioxide is replaced with an equal amount of acid-etched modified nano-titanium dioxide-cerium oxide composite fibers in embodiment 1. The preparation method of the acid-etched modified nano-titanium dioxide-cerium oxide composite fibers is as follows:
[0041] Acid-modified nano-titanium dioxide and cerium oxide powders were mixed in a mass ratio of 3:2, dispersed in water, and 20wt% of PVP by water mass was added to obtain a spinning solution, and electrospinning was performed: the spinning voltage was 15KV, and the spinning distance was 14cm, and titanium dioxide-cerium oxide / PVP fibers were obtained on a receiving substrate; then, the titanium dioxide-cerium oxide / PVP fibers were heated to 800°C at 3°C / min for aerobic calcination to obtain acid-modified nano-titanium dioxide-cerium oxide composite fibers.
[0042] Example 8
[0043] In this embodiment, in Example 2, the acid-etched modified nano-titanium dioxide is replaced with an equal amount of acid-etched modified nano-titanium dioxide-cerium oxide composite fibers. The preparation method of the acid-etched modified nano-titanium dioxide-cerium oxide composite fibers is shown in Example 7.
[0044] Example 9
[0045] In this embodiment, in Example 3, the acid-etched modified nano-titanium dioxide is replaced with an equal amount of acid-etched modified nano-titanium dioxide-cerium oxide composite fibers. The preparation method of the acid-etched modified nano-titanium dioxide-cerium oxide composite fibers is shown in Example 7.
[0046] Example 10
[0047] In this embodiment, in Example 4, the acid-etched modified nano-titanium dioxide is replaced with an equal amount of acid-etched modified nano-titanium dioxide-cerium oxide composite fibers. The preparation method of the acid-etched modified nano-titanium dioxide-cerium oxide composite fibers is shown in Example 7.
[0048] Embodiment 11
[0049] In this embodiment, in Example 5, the acid-etched modified nano-titanium dioxide is replaced with an equal amount of acid-etched modified nano-titanium dioxide-cerium oxide composite fibers. The preparation method of the acid-etched modified nano-titanium dioxide-cerium oxide composite fibers is shown in Example 7.
[0050] Example 12
[0051] In this embodiment, in Example 6, the acid-etched modified nano-titanium dioxide is replaced with an equal amount of acid-etched modified nano-titanium dioxide-cerium oxide composite fibers. The preparation method of the acid-etched modified nano-titanium dioxide-cerium oxide composite fibers is shown in Example 7.
[0052] Comparative Example 1
[0053] This comparative example is to replace the acid-etched modified nano titanium dioxide of Example 1 with an equal amount of ordinary anatase nano titanium dioxide (i.e., nano titanium dioxide before acid-etching modification, with a specific surface area of 150 m 2 The contents and specifications of the other components are the same as those in Example 1.
[0054] Comparative Example 2
[0055] This comparative example is that in Example 1, the magnesium phosphate cement in Example 1 is replaced by ordinary Portland cement (p.042.5). The contents and specifications of the remaining components are the same as those in Example 1.
[0056] The coating material of the present invention is used in the following manner: pure water is added according to a water-cement ratio of 0.38-0.42, mixed with a vibrating mixer for 2-3 minutes, and applied and scraped on the surface of the concrete structure affected by back water pressure with a trowel, with a scraping thickness of 1-5 mm, and dried naturally.
[0057] Constructing a hydraulic underground powerhouse model: Prepare a square concrete test board with a smooth surface, 4 cm thick, 45 cm long and wide. Use silicone sealant to glue a plastic bucket with a bottom removed on one side of the concrete test board. Place the concrete test board flat on a 25×40 cm transparent plastic storage box. After the glue has dried for 24 hours, add 40 cm of water to the bucket, add 8% sodium chloride to increase the water pressure, and seal the bucket cover with silicone sealant to prevent evaporation.
[0058] The coating materials prepared in the above embodiments and comparative examples are scraped on the lower surface of the concrete test plate. The scraping method is: add pure water to the coating material at a water-cement ratio of 0.4, use a vibrating mixer to mix and mix for 2 minutes, and scrape it to the lower surface of the concrete test plate. The scraping thickness is 3-4mm, and the 1 / 2 side of the storage box is also scraped with a coating material with a thickness of 1-2mm. 0.25ppm of formaldehyde was added to the plastic storage box, and the initial air humidity was measured to be 40%. The silicone sealant gun was used again to apply the gap between the concrete test plate and the plastic storage box. The entire test device was placed in a partition in a dark room (temperature of 25-28°C), and a glass test bench was provided in each partition, and a 36W spotlight was installed under the test bench to illuminate the storage box. After the experiment was carried out for 10 days, a small electric drill was used to drill holes in the storage box, and humidity and formaldehyde probes were placed in them respectively. During the test, the probes and the holes were sealed. After 10 days of each experiment, the air humidity in the storage box, the change of formaldehyde concentration, the mold growth on the lower surface of the concrete test board and the integrity of the coating were statistically analyzed. The statistical results are recorded in Table 1.
[0059] Table 1: Comparison of moisture and mildew resistance and air purification of each group of coating materials
[0060] Group Air humidity Formaldehyde concentration Mold Coating conditions Example 1 40.9% 0.07ppm No mold spots intact Example 2 40.6% 0.10ppm No mold spots intact Example 3 40.7% 0.06ppm No mold spots intact Example 4 40.9% 0.10ppm No mold spots intact Example 5 40.3% 0.08ppm No mold spots intact Example 6 40.7% 0.10ppm No mold spots intact Example 7 40.4% 0.03ppm No mold spots intact Example 8 40.6% 0.05ppm No mold spots intact Example 9 40.9% 0.00ppm No mold spots intact Example 10 41.0% 0.05ppm No mold spots intact Embodiment 11 41.4% 0.03ppm No mold spots intact Example 12 40.8% 0.06ppm No mold spots intact Comparative Example 1 40.6% 0.19ppm No mold spots intact Comparative Example 2 44.5% 0.07ppm There are mold spots crack
[0061] After the experiment, only Comparative Example 2 showed mildew spots on the coating materials in the above embodiments and comparative examples. This may be because the bonding force and early strength of ordinary Portland cement are insufficient, affecting the waterproof performance, the air humidity in the plastic box is relatively high, and moisture penetration causes partial damage to the coating material layer, which promotes the growth of mold. Although the coating material prepared in Comparative Example 1 has no mildew spots on the surface, its air purification efficiency slows down under 36W artificial light.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. These modifications or replacements, or the technical features in the above embodiments may be combined in the manner described in the embodiments if they do not conflict with each other, and these modifications, replacements or combinations do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A multifunctional coating material for a concrete structure surface affected by back water pressure, characterized in that: Measured by mass percentage, the composition includes: 30-40% phosphate magnesium cement, 10-15% fly ash, 30-40% limestone machine-made sand, 5-10% acid-etched modified nano titanium dioxide or its composite, 5-10% kyanite powder, 3-5% fluorocarbon resin, 0.5-1% ultra-high molecular weight polyethylene fiber and 0.5-1% ternary high-efficiency retarder; the multifunctional coating material is a powder material.
2. The multifunctional coating material according to claim 1, characterized in that: The fineness of magnesium phosphate cement is below 80μm, that is, the percentage passing through the 80μm sieve should be greater than 90%, and the specific surface area is 300-400m 2 / kg.
3. The multifunctional coating material according to claim 1, characterized in that: The average particle size of fly ash is less than 10μm, 70% of the particles should be able to pass through a 45μm sieve, and the specific surface area is 300-600m 2 / kg.
4. The multifunctional coating material according to claim 1, characterized in that: The maximum particle size of the limestone machine-made sand is 0.3 mm, and the preferred content of the limestone machine-made sand in the coating material is 32-36%. The limestone machine-made sand contains 1-5% of magnesium carbonate by mass of the coating material.
5. The multifunctional coating material according to claim 1, characterized in that: The particle size of the acid-etched modified nano titanium dioxide does not exceed 100nm, and the specific surface area is extremely large, reaching 50-250m 2 / g.
6. The multifunctional coating material according to claim 1, characterized in that: The preparation method of acid-etched modified nano titanium dioxide is as follows: Using nano-TiO2 as raw material, disperse nano-TiO2 in an appropriate amount of deionized water to form a suspension, slowly add an inorganic acid solution with a concentration of 0.1M-6M to the suspension, continue stirring to ensure uniform mixing, control the temperature at 35-85℃ for 0.5-3h, after the acid etching treatment, wash the sample with deionized water until the pH value of the washing water is close to neutral, separate the solid and liquid, collect, dry, and calcine in air at 400-600℃ for 1-3h.
7. The multifunctional coating material according to claim 1, characterized in that: The acid-etched modified nano titanium dioxide composite is an acid-etched modified nano titanium dioxide-cerium oxide composite fiber, and its preparation method is as follows: Acid-modified nano titanium dioxide and cerium oxide powder are mixed in a mass ratio of 3:1-2, dispersed in water, and 10-20wt% of PVP by water mass is added to obtain a spinning solution, and electrostatic spinning is performed; the electrostatic spinning monomer conditions are: a spinning voltage of 10-20KV, a spinning distance of 13-16cm, and titanium dioxide-cerium oxide / PVP fibers are obtained; then, the titanium dioxide-cerium oxide / PVP fibers are heated to 750-850°C at 3-5°C / min for aerobic calcination to obtain acid-modified nano titanium dioxide-cerium oxide composite fibers.
8. The multifunctional coating material according to claim 1, characterized in that: The particle size of the kyanite powder is 1-10 μm; the fluorocarbon resin is a combination of fluorinated ethylene propylene copolymer FEVE and hexafluoropropylene-vinyl ether copolymer in a ratio of 3-5:1-2.
9. The multifunctional coating material according to claim 1, characterized in that: The length of the ultra-high molecular weight polyethylene fiber is 3-19 mm; the diameter is about 10-40 μm, and the molecular weight of the ultra-high molecular weight polyethylene fiber is 3 million to 6 million Daltons.
10. The multifunctional coating material according to claim 1, characterized in that: The ternary high-efficiency retarder is obtained by combining borax, calcium chloride and sodium phosphate in a mass ratio of 3-4:4-5:3-4, and is a micron-grade fine powder.